PERAN MODAL SOSIAL FILSAFAT TRI TANGTU SILIH DALAM PEMBERDAYAAN EKONOMI MASYARAKAT DI DESA ALAMENDAH RANCABALI BANDUNG - Masruri, Siswanto; Fauroni, R Lukman (INFERENSI, 2013)
The economic empowerment of communities often tend to focus on the aspect of method and program, which is mostly imported and western-minded. Social capital may be opimized to make sure that the economic empowerment achieving its goals. In some conditon, the social capital philosophy of tri tangtu silih asih silih asah and silih asuh plays a significant role in ensuring the success of a community economic empowerment. This paper is a study of social system of community economic empowerment aiming on understanding the background condition of the economic empowerment of a village community with particular case of the village farmer group. Keywords: The Social Capital Role, Philosophy of Tri Tangtu Silih, Economic Empowerment.